Neuromuscular parameters and anaerobic power of U-20 futsal players - Kassiano, W.; Andrade, A. D.; de Jesus, K.; Barroso Lima, A.; Simim, M. A.; Araripe Medeiros, A. I.; de Oliveira Assumpção, C. (Journal of Human Sport & Exercise, 2019)
The current investigation aimed to find the difference between right and left lower limb strength of quadriceps and hamstring muscles and describe young futsal players` explosive strength and anaerobic power. The study comprised 12 university male U-20 futsal players (74.5 ± 9.7 kg;173.2 ± 7.2 cm; 18.7 ± 1.2 yrs.). Isometric strength was measured using an isometric dynamometer, lower limb explosive strength was assessed through the Countermovement Jump and anaerobic power was estimated with the Wingate test. Initially, results were displayed through descriptive statistics. Magnitude-based inference with respective Confidence Intervals (CI=90%) and effect size were used to compare inter-lower limb strength. No substantial differences were found between right and left lower limb, to knee extension and flexion. Team`s explosive strength and anaerobic power were 36.7 ± 7 cm and 998.3 ± 125.9 W, respectively. These findings suggest that young futsal players` performance may be less affected due to inter-lower limb asymmetries.